The application of green solvent in a biorefinery using lignocellulosic biomass as a feedstock. (1st April 2022) - New, Eng Kein; Tnah, Shen Khang; Voon, Khai Shing; Yong, Khai Jie; Procentese, Alessandra; Yee Shak, Katrina Pui; Subramonian, Wennie; Cheng, Chin Kui; Wu, Ta Yeong
Abstract: The high dependence on crude oil for energy utilization leads to a necessity of finding alternative sustainable resources. Solvents are often employed in valorizing the biomass into bioproducts and other value-added chemicals during treatment stages. Unfortunately, despite the effectiveness of conventional solvents, hindrances such as expensive solvents, unfavourable environmental ramifications, and complicated downstream separation systems often occur. Therefore, the scientific community has been actively investigating more cost-effective, environmentally friendly alternatives and possess the excellent dissolving capability for biomass processing. Generally, 'green' solvents are attractive due to their low toxicity, economic value, and biodegradability. Nonetheless, green solvents are not without disadvantages due to their complicated product recovery, recyclability, and high operational cost. This review summarizes and evaluates the recent contributions, including potential advantages, challenges, and drawbacks of green solvents, namely ionic liquids, deep eutectic solvents, water, biomass-derived solvents and carbon dioxide in transforming the lignocellulosic biomass into high-value products. Moreover, research opportunities for future developments and potential upscale implementation of green solvents are also critically discussed. Graphical abstract: Image 1 Highlights: Recent applications of green solvents in biorefinery are discussed. H2 O and CO2 are presented as relatively abundant and low-cost green solvents. [Emim][Ac], ChCl:urea and γ-valerolactone offer low-severity biorefineries. Recyclability of green solvents is crucial for their economic feasibilities. Except for H2 O and CO2, toxicities of most green solvents remain inconclusive.